Socio-Demographic, Nutritional Status, Risk Of Falls Toward Sarcopenia Among Community-Dwelling Elderly - Sumandar Sumandar; Rifa Yanti; Rohmi Fadhli (Universitas STRADA Indonesia, 2021)
Sarcopenia is a condition of muscle degeneration, occurs due to multifactorial aging process and have impact toward increase mortality . The purpose was to analyze correlation Socio-demographic , Nutrition, Risk of fall toward sarcopenia among community Dwelling Elderly in the Pekanbaru. Cross sectional study was conducted among 275 elderly selected by cluster sampling. Data were collected using questionnaires and analyzed using Chi-square test analyses. There was a positive correlation between gender ( 0,023), marital status ( 0,019), Education level ( 0,033), nutrition status ( 0,014),Risk of fall ( 0,008) toward Sarcopenia. Suggestions for research, it is necessary to have further research related factors of Sarcopenia. For nurses, it is better provide health education regarding factors that may be changed in elderly, should collaboration to stakeholder such as general practitioners, nutritionist, physiotherapist, family, making policy.